Explore a New Direction for the Treatment of Diabetic Nephropathy by High-Throughput Sequencing - Yu Zhou; Qingyuan Li; Hui Zhu; Zhihui Yao; Yisheng Wang; Zhui Ke (Asia Pacific Journal of Clinical Medical Research, 2026)
Objective: To screen out miRNAs and mRNAs with targeted binding relationship, DKD-related signaling pathways and potential therapeutic drugs related to diabetic kidney disease ( DKD ), and to explore new directions for DKD treatment from the gene, signaling pathway and drug levels. Methods: Using the R language, differential miRNAs and mRNAs related to DKD were screened from the high-throughput sequencing data set of the GEO database. DKD-related signals were obtained by KEGG analysis. TargetScan database was used to further screen out miRNAs and mRNAs with targeted interaction. The DSigDB database was used to find out the drug components that had targeted effects on the proteins corresponding to the differential mRNA, and the binding stability of the two was verified by molecular docking. Results: A total of 17 miRNAs with a difference of more than 2 times, 68 mRNAs with a difference of more than 1.5 times, and 7 mRNAs with a difference of more than 4 times were obtained from the GEO database. KEGG analysis showed that DKD-related signaling pathways were IL-17 signaling pathway, NF-κB signaling pathway, TGF-β signaling pathway, TNF signaling pathway, etc. The TargetScan database further screened 7 miRNAs with targeted interaction and 26 mRNAs with targeted interaction. Through the DSigDB database, 51 drug components with potential treatment of DKD, such as acetovanillone, ademetionine, betacarotene, pterostilbene, and 5 corresponding target gene proteins were obtained : OLR1, IL1B, SERPINB2, CXCL3, ALAS2. Molecular docking showed that the drug components were stable in binding to the target gene protein. Conclusion: Hsa-miR-142-5p, hsa-miR-1225-3p, hsa-miR-513a-5p and OLR1, IL1B, ALAS2 mRNA can be used as key targets for the prevention and treatment of DKD. IL-17, NF-κB, TGF-β, TNF and other signaling pathways play an important regulatory role in the pathological process of DKD, and are the core related pathways for intervening DKD. In addition, natural active ingredients and compounds such as vanillone, adenosylmethionine, β-carotene, and pterostilbene showed good potential therapeutic value for DKD. The above research results can provide theoretical basis and new ideas for the exploration of the mechanism of DKD, targeted intervention and the development of new prevention and treatment strategies, and lay a research foundation for improving the clinical prognosis and alleviating the progression of DKD patients.